1995
DOI: 10.1016/0014-5793(95)00209-r
|View full text |Cite
|
Sign up to set email alerts
|

The endozepine ODN stimulates polyphosphoinositide metabolism in rat astrocytes

Abstract: Astrocytes synthesize a series of peptides called endozepines which act as endogenous ligands of benzodiazepine receptors. The present study demonstrates that the endozepine ODN causes a dose-dependent increase in inositoi trisphosphate and a parallel decrease in phosphatidylinositoi bisphosphate in cultured rat astrocytes. Pre-incubation of astrocytes with the phospholipase C inhibitor U 73122 or with pertussis toxin totally blocked polyphosphoinositide metabolism. These data show that, in rat astrocytes, ODN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…Consistent with this finding, it has been recently shown that, in rat Leydig cells, endozepines stimulate testosterone secretion via a PBRindependent mechanism (Garnier et al 1993). It has also been found that, in rat astrocytes, the endozepine ODN activates a membrane receptor positively coupled to a phospholipase C through a pertussis toxin-sensitive G protein (Patte et al 1995, Lamacz et al 1996, Gandolfo et al 1997. Further studies on the mechanism of action of TTN are required to elucidate the type of receptor responsible for the effect of the peptide on adrenocortical cells.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with this finding, it has been recently shown that, in rat Leydig cells, endozepines stimulate testosterone secretion via a PBRindependent mechanism (Garnier et al 1993). It has also been found that, in rat astrocytes, the endozepine ODN activates a membrane receptor positively coupled to a phospholipase C through a pertussis toxin-sensitive G protein (Patte et al 1995, Lamacz et al 1996, Gandolfo et al 1997. Further studies on the mechanism of action of TTN are required to elucidate the type of receptor responsible for the effect of the peptide on adrenocortical cells.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, DBI acts as an acyl-CoAbinding protein (Knudsen et al 1989), suggesting that it may exert a physiological role as a lipid-transport protein (Mikkelsen & Knudsen 1987). Recent studies conducted in rat astrocytes indicated that endozepines may also activate a membrane receptor positively coupled to a phospholipase C through a pertussis toxin-sensitive G protein (Patte et al 1995, Lamacz et al 1996, Gandolfo et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that several of the effects induced by ODN are mediated via a G-proteincoupled receptor. In particular, in vitro studies have shown that ODN increases intracellular calcium concentration in cultured rat astrocytes through activation of a metabotropic receptor positively coupled to phospholipase C (Patte et al, 1995;Gandolfo et al, 1997). We have previously observed that the inhibitory effect of ODN on feeding behavior is not affected by diazepam, a mixed CBR and PBR agonist (Garcia de Mateos-Verchere et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…TTN acts preferentially through peripheral-type benzodiazepine receptors (PBR) located either at the outer mitochondrial membrane or at the plasma membrane level Berkovich et al, 1990;Gandolfo et al, 2001). Finally, ODN can also activate a metabotropic receptor positively coupled to phospholipase C through a pertussis toxin-sensitive G-protein (Patte et al, 1995;Gandolfo et al, 1997). We have previously shown that the anorexigenic effect of ODN was not affected by the mixed CBR/PBR agonist diazepam (Garcia de MateosVerchere et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, endozepines may interact with central-and peripheral-type benzodiazepine receptors, which are both expressed in the CNS (Costa et al, 1991;Papadopoulos et al, 1992). Concurrently, it has been reported that ODN can also stimulate the activity of astrocytes by interacting with a novel type of receptor pharmacologically and functionally distinct from the classical benzodiazepine receptors (Gandolfo et al, 1997;Patte et al, 1995).…”
Section: Introductionmentioning
confidence: 95%